Variable-density low-damage polymer-particle composite gel temporary plugging agent
By using a variable density low-damage polymer-particle composite gel temporary plugging agent, using weighted salt to adjust the density and pre-crosslinked particles to form a skeleton, the polymer and cross-linking agent are cross-linked to form a network structure, which solves the problem of leakage of existing gel temporary plugging agents under the pressure difference between the wellbore and the formation, achieves high temperature stability and reservoir protection, and reduces construction costs.
Patent Information
- Application Number
- CN202510804474.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2025-09-19
AI Technical Summary
Existing variable density gel temporary plugging agents are prone to leaking into the formation under the pressure difference between the wellbore and the formation, causing reservoir damage. In addition, they have poor stability in high temperature environments and are difficult to meet the sealing requirements of the wellbore and reservoir.
A variable density low-damage polymer-particle composite gel temporary plugging agent is used. The density is adjusted by adding salt, the pre-crosslinked particles form a skeleton, the polymer and the crosslinking agent cross-link to form a network structure, the viscosity and curing time are controlled, the polymer loss is reduced, and the mechanical strength is enhanced.
It maintains good stability in a wide temperature range (70-170°C), reduces reservoir damage, achieves wellbore sealing, can chemically break gel, has good compatibility with different brine well-pressing fluids, and reduces construction costs.
Smart Images

Figure CN120665578A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oilfield chemistry, and in particular relates to a variable-density low-damage polymer-particle composite gel temporary plugging agent. Background Art
[0002] China's natural gas fields are primarily located in the central and western regions, while the largest natural gas consumption markets are primarily located in the eastern coastal areas. Due to the frequent injection and production of gas storage facilities over long periods of time, the pressure in gas wells and reservoirs fluctuates frequently, which can easily lead to problems such as wellbore cement sheath failure and wellbore corrosion. This can cause gas channeling and natural gas leaks, frequently necessitating workovers. To minimize well construction difficulty and facilitate gas injection and production, gas storage facilities are typically constructed in medium- to high-permeability reservoirs, with 95% of these facilities located at depths below 2,500 meters. Furthermore, most reservoirs have an ambient temperature distribution below 165°C and a pressure coefficient below 1.13, as shown in Table 1. This effectively reduces the challenges of reservoir construction and subsequent maintenance. Temporary plugging of injection and production wells in gas storage facilities requires both preventing the loss of upper kill fluid and preventing natural gas from entering the wellbore from the lower reservoir.
[0003] Variable density, high temperature resistant polymer gel temporary plugging fluid is a current research hotspot. Due to its good injectability, plugging ability, and easy unplugging properties, it is often used as a temporary plugging material for oil and gas wells. Its main types include in-situ polymer gel, pre-crosslinked gel particles, nanoparticles, and mixed types of polymer plugging agents. Currently, conventional in-situ polymer gel temporary plugging agents are prone to leaking into the formation in large quantities under the pressure difference between the wellbore and the formation, which is not conducive to reservoir protection. At the same time, it causes material waste and increases construction costs. Among them, the foam gel has low density and the foam stability is easily affected by the reservoir temperature and formation water salinity, making it difficult to apply universally. Pre-crosslinked gel particles alone have problems such as high requirements for pore and fracture size matching, difficulty in unplugging, and high cost. Summary of the Invention
[0004] In order to solve at least one of the above problems, the present invention provides a variable density low damage polymer-particle composite gel temporary plugging agent, which has an adjustable density (1.00-1.3 g / cm 3 ), wide operating temperature range (70-170℃), high gel strength, adjustable curing time, chemical gel breaking, controllable polymer loss and good compatibility with different brine well-pressing fluids.
[0005] The technical solution of the present invention is: take a certain amount of hydrophilic agent, add weighting salt while stirring to completely dissolve it, then add crosslinker 1 and crosslinker 2 respectively and stir for 10 minutes, add pre-crosslinked particles, stir for 10 to 120 minutes to fully swell them (the higher the weighting salt concentration of the system, the longer the swelling time of the pre-crosslinked particles), then add polymer, stir for 1 to 12 hours to completely dissolve it (the higher the weighting salt concentration of the system, the longer the dissolution time of the polymer), and obtain a polymer solution.
[0006] The weighted salt mentioned above is primarily used to increase the system density for better compatibility with the kill fluid. It also effectively controls the viscosity and curing time of the variable-density, low-damage polymer-particle composite gel temporary plugging agent. The main mechanism is as follows: During on-site construction, the temporary plugging system is pumped to the bottom of the well, and the kill fluid is pumped in from above. This weighted composite gel temporary plugging agent prevents it from floating under the action of the kill fluid. Furthermore, the salt water inhibits polymer dissolution (restraining of long-chain and branched molecules), partially suppressing the high viscosity caused by the high polymer viscosity and providing favorable pumping conditions during on-site construction. Furthermore, salt ions may participate in the polymer re-crosslinking process, and controlling the density of the composite gel temporary plugging agent can regulate the gelation time. Furthermore, the pre-crosslinked particles in the composite gel temporary plugging agent can form a temporary plugging layer at the wellbore during the plugging process, reducing or preventing polymer loss and minimizing reservoir damage. After gelation, the particles in the variable-density, low-damage polymer-particle composite gel temporary plugging agent act as a backbone, increasing the mechanical strength of the temporary plugging agent and improving its pressure-bearing capacity. The gelling process is as follows: The aforementioned polymers AKYPM-6S, KYPM-10, AN113SH, and HENGFLOC81207 are primarily produced by polymerization of monomers such as acrylamide (AM) and 2-acrylamido-2-methylpropanesulfonic acid (AMPS), and all contain one or more of amino (-NH2), hydroxyl (-OH), carboxyl (-COOH), and amide (-NH-CO-) groups. The aforementioned pre-crosslinked particles, such as the flexible colloidal particles KA01, 220A, and SPG-326, contain one or more of carboxyl (-COOH), hydroxyl (-OH), and amide (-CONH2) groups. Crosslinker 1 contains an amino group. Crosslinker 2 is primarily a metal ion crosslinker. Crosslinker 1 can react with carboxyl groups (-COOH) to form amide bonds, while crosslinker 2 can react with carboxylate ions. Under the action of the cross-linking agent, the polymer molecules and the pre-cross-linked particles are entangled and cross-linked to form a stable network structure, which is gelled and solidified. Some anions in the weighted salt (such as potassium pyrophosphate) can also act as a cross-linking agent to participate in the cross-linking reaction and increase the degree of cross-linking.
[0007] Theoretically, any of the aforementioned weighted salts, polymers, pre-crosslinked particles, crosslinker 1, and crosslinker 2 can be used in the present invention. Furthermore, the inventors have discovered that, in addition to regulating gelation time by forming a network structure through crosslinking the polymer, the aforementioned crosslinker can also regulate system viscosity and gel-breaking time.
[0008] In one embodiment of the present invention, the density of the variable density low damage polymer-particle composite gel temporary plugging agent is 1.00-1.3 g / cm 3 .
[0009] Compared with the prior art, the present invention has the following beneficial effects:
[0010] The variable density low-damage polymer-particle composite gel temporary plugging agent of the present invention has good high-temperature stability. After aging for 12 days at 165°C, the free water mass is less than 1 ml, and the solid plug is intact. After aging for 20 days at 80°C, the free water mass is less than 10 ml, and the temporary plugging agent still has high strength at this time. The above aging time shows that the temporary plugging agent proposed by the present invention has good mechanical properties within the on-site construction time, which can ensure the smooth completion of the temporary plugging construction. Compared with conventional temporary plugging plugs, it has the ability to chemically break the gel. Under the action of 10% sodium persulfate, under an environment of 70 to 170°C, the variable density low-damage polymer-particle composite gel temporary plugging agent can completely break the gel within 10 hours, and the solid phase residual mass is 0g, indicating that the composite gel temporary plugging agent proposed by the present invention causes little reservoir damage. The variable density low-damage polymer-particle composite gel temporary plugging agent has good compatibility with salt water well pressure fluids of the same density. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 Schematic diagram of the compatibility test between composite gel temporary plugging agent and brine well-killing fluid
[0012] Figure 2 Example 1: Free water diagram of aging of variable density low-damage polymer-particle composite gel temporary plugging agent
[0013] Figure 3 Example 1 Variable Density Low Damage Polymer-Particle Composite Gel Temporary Plugging Agent Gel Breaking Efficiency Diagram
[0014] Figure 4 Example 2: Free water diagram of aging of variable density low damage polymer-particle composite gel temporary plugging agent
[0015] Figure 5 Example 2 Variable Density Low Damage Polymer-Particle Composite Gel Temporary Plugging Agent Gel Breaking Efficiency Diagram
[0016] Figure 6 Example 3: Free water diagram of aging of variable density low-damage polymer-particle composite gel temporary plugging agent
[0017] Figure 7 Example 3 Variable Density Low Damage Polymer-Particle Composite Gel Temporary Plugging Agent Gel Breaking Efficiency Diagram
[0018] Figure 8 Example 4: Free water diagram of aging of variable density low-damage polymer-particle composite gel temporary plugging agent
[0019] Figure 9 Example 4 Variable Density Low Damage Polymer-Particle Composite Gel Temporary Plugging Agent Gel Breaking Efficiency Diagram DETAILED DESCRIPTION
[0020] The present invention will be further described in detail below with reference to the embodiments and the accompanying drawings, but the embodiments of the present invention are not limited thereto.
[0021] In the following examples, unless otherwise specified, the raw materials used are conventional commercial products.
[0022] In the following examples, unless otherwise specified, the methods used are conventional methods in the art.
[0023] In the following examples, the high temperature resistance was measured using the following method:
[0024] In static experiments, a constant temperature oven is used to maintain a constant temperature for the plug system to observe its static thermal stability. Degradation of temporary plugs is characterized by measuring the free water content and physical flow morphology after aging for a certain period of time. After preparing the polymer solution, the aging process continues, with the free water content measured every two days and the plug morphology observed.
[0025] In the following examples, the gel breaking performance was measured using the following method:
[0026] Weigh 20g of variable density low-damage polymer-particle composite gel temporary plugging agent and place it in an aging tank. Then add 100ml of gel-breaking liquid (10wt% sodium persulfate solution) and seal the aging tank. Place the aging tank in an electric constant temperature drying oven and set the temperature to the temperature of different system plug aging (such as 85℃, 165℃, etc.). Take out the aging tank every 2 hours and cool it to room temperature. Then separate the residual solid phase by suction filtration and weigh it. The gel-breaking efficiency is calculated by the following formula:
[0027] Y=(m0-m1) / m0*100%
[0028] Where Y is the breaking efficiency, %; m0 is the mass of the rubber plug before breaking, g; m1 is the mass of the remaining solid phase after breaking, g;
[0029] In the following examples, the compatibility properties were measured using the following method:
[0030] During the experiment, an aging tank was used to simulate a wellbore. The composite gel temporary plugging agent and the killing fluid were added in a volume ratio of 1:3 into the aging tank and a 100ml transparent graduated cylinder. First, the floating and sinking of the composite gel temporary plugging agent in the graduated cylinder and the dissolution of the polymer were observed (e.g. Figure 1 The aging tank was then sealed and aged at a certain temperature for 10 hours, and the gel formation in the presence of salt water well-killing fluid was observed.
[0031] Example 1
[0032] This embodiment provides a raw material ratio and preparation method for a variable-density, low-damage polymer-particle composite gel temporary plugging agent. The raw materials, measured in mass percentage, comprise 20 wt% weighting salt (relative to the mass of clean water, the same below), which is potassium pyrophosphate, a certain mass of clean water, 2 wt% crosslinker 1, and 1 wt% crosslinker 2, where crosslinker 1 is polyethyleneimine (PEI), and crosslinker 2 is a 1:1 mixture of chromium acetate and borax. The agent also comprises 1 wt% pre-crosslinked particles, which are a 1:1 mixture of flexible colloidal particles KA01 and flexible colloidal particles 220A. The agent also comprises 2 wt% polymer, which is a 1:1 mixture of AN113SH and KYPM-10.
[0033] This embodiment also provides a method for preparing a variable density low-damage polymer-particle composite gel temporary plugging agent:
[0034] Take 20g of potassium pyrophosphate, add it into 100ml of water and stir to dissolve. The solution becomes clear and transparent with a density of 1.15g / cm 3 Then, 2g of polyethyleneimine (PEI), 0.5g of chromium acetate, and 0.5g of borax were added to the mixture and stirred for 10 minutes. Then, 0.5g of flexible colloidal particles KA01 and 0.5g of flexible colloidal particles 220A were added and stirred until fully swollen. Finally, 1.0g of AN113SH and 1.0g of KYPM-10 were added and stirred for 10 hours until the polymer was completely dispersed and dissolved to obtain a polymer solution. The polymer solution was poured into an aging tank, sealed, and aged in a constant temperature oven at 165°C for 24 hours to obtain a variable density, low-damage polymer-particle composite gel temporary plugging agent.
[0035] In this embodiment, the variable density low damage polymer-particle composite gel temporary plugging agent has a free water content of less than 1 ml after aging at 165°C for 12 days. Figure 2 The rubber plug is complete in shape and has a clear outline. It can be completely broken at 165℃, with a breaking efficiency of 100% in 8 hours. Figure 3 In compatibility experiments, the composite gel temporary plugging agent did not float in the saline well-killing fluid. Furthermore, when the composite gel temporary plugging agent coexists with the saline well-killing fluid, it does not dissolve into the upper well-killing fluid and become diluted. After aging with the saline well-killing fluid, the composite gel temporary plugging agent gels well with the saline well-killing fluid. The rubber plugs in each kettle group exhibited excellent shape and adhered tightly to the metal kettle wall, ensuring wellbore sealing.
[0036] Example 2
[0037] This embodiment provides a raw material ratio and preparation method for a variable-density, low-damage polymer-particle composite gel temporary plugging agent. The raw materials of the variable-density, low-damage polymer-particle composite gel temporary plugging agent, measured in mass percentage, include 20 wt% weighting salt (relative to the mass of clean water, the same below), wherein the weighting salt is sodium chloride, potassium chloride, sodium formate, and potassium formate, mixed in equal mass ratios, and a certain mass of clean water. The raw materials also include 1 wt% crosslinker 1 and 0.5 wt% crosslinker 2, wherein crosslinker 1 is polyethyleneimine (PEI), and crosslinker 2 is a 1:1 mixture of zinc acetate and borax. The raw materials also include 1 wt% pre-crosslinked particles, wherein the crosslinked particles are a 1:1 mixture of flexible colloidal particles KA01 and flexible colloidal particles SPG-326. The raw materials also include 1 wt% polymer, wherein the polymer is a 1:1 mixture of AKYPM-6S and HENGFLOC81207.
[0038] The preparation method of the variable density low-damage polymer-particle composite gel temporary plugging agent in this embodiment is the same as that in Example 1 and will not be further described.
[0039] In this embodiment, after aging at 170°C for 12 days, the free water content of the variable density low damage polymer-particle composite gel temporary plugging agent is 2.86 ml. Figure 4 The rubber plug has a complete shape, but no clear outline edge. It can be completely broken at 170℃, with a breaking efficiency of 100% in 6 hours. Figure 5 The composite gel temporary plugging fluid proposed in this example does not float or dissolve in saline well-killing fluid of the same density, and after aging, the composite gel temporary plugging fluid partially gels and solidifies, indicating that the composite gel temporary plugging fluid proposed in this example has good compatibility with saline well-killing fluid of the same density.
[0040] Example 3
[0041] This embodiment provides a raw material ratio and preparation method for a variable-density, low-damage polymer-particle composite gel temporary plugging agent. The raw materials, measured in mass percentage, comprise 0.5 wt% weighting salt (relative to the mass of clean water, the same below), wherein the weighting salt is a 1:1 mixture of sodium chloride and potassium phosphate, and a certain mass of clean water. The raw materials also include 1 wt% crosslinker 1 and 0.5 wt% crosslinker 2, wherein crosslinker 1 is polyethyleneimine (PEI), and crosslinker 2 is a 1:1 mixture of zinc acetate and borax. The raw materials also include 0.5 wt% pre-crosslinked particles, wherein the crosslinked particles are a 1:1 mixture of flexible colloidal particles KA01 and flexible colloidal particles 220A. The raw materials also include 1 wt% polymer, wherein the polymer is a 1:1 mixture of AN113SH and KYPM-10.
[0042] The preparation method of the variable density low-damage polymer-particle composite gel temporary plugging agent in this embodiment is the same as that in Example 1 and will not be further described.
[0043] In this embodiment, after the variable density low damage polymer-particle composite gel temporary plugging agent is aged at 80°C for 20 days, the free water content is 8.73 ml. Figure 6 The rubber plug has a complete shape and a clear edge. It can be completely broken at 80℃, with a breaking efficiency of 100% in 10 hours. Figure 7 The composite gel temporary plugging fluid proposed in this example does not float or dissolve in saline well-killing fluid of the same density, and after aging, the composite gel temporary plugging fluid partially gels and solidifies, indicating that the composite gel temporary plugging fluid proposed in this example has good compatibility with saline well-killing fluid of the same density.
[0044] Example 4
[0045] This embodiment provides a raw material ratio and preparation method for a variable-density, low-damage polymer-particle composite gel temporary plugging agent. The raw materials, measured by mass percentage, comprise 0.5 wt% weighting salt (relative to the mass of clean water, the same below). The weighting salt is a mixture of potassium monohydrogen phosphate, potassium dihydrogen phosphate, potassium pyrophosphate, and potassium phosphate in equal proportions. The agent also contains 0.8 wt% crosslinker 1 and 0.2 wt% crosslinker 2, where crosslinker 1 is polyethyleneimine (PEI) and crosslinker 2 is chromium acetate. The agent also contains 0.4 wt% pre-crosslinked particles, where the crosslinked particles are flexible colloidal particles 220A. The agent also contains 0.8 wt% polymer, where the polymer is KYPM-10.
[0046] The preparation method of the variable density low-damage polymer-particle composite gel temporary plugging agent in this embodiment is the same as that in Example 1 and will not be further described.
[0047] In this embodiment, after the variable density low damage polymer-particle composite gel temporary plugging agent is aged at 70°C for 20 days, the free water content is 9.32 ml. Figure 8 The rubber plug has a complete shape and a clear edge. It can be completely broken at 70℃, with a breaking efficiency of 100% in 8 hours. Figure 9 The composite gel temporary plugging fluid proposed in this example does not float or dissolve in saline well-killing fluid of the same density, and after aging, the composite gel temporary plugging fluid partially gels and solidifies, indicating that the composite gel temporary plugging fluid proposed in this example has good compatibility with saline well-killing fluid of the same density.
[0048] Example 5
[0049] This embodiment provides a raw material ratio and preparation method for a variable-density, low-damage polymer-particle composite gel temporary plugging agent. The raw materials, measured by mass percentage, comprise 30 wt% weighting salt (relative to the mass of clean water, the same below). The weighting salt is a mixture of equal weights of sodium formate, potassium formate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate, and sodium phosphate. A certain mass of clean water is also included. The raw materials also include 1 wt% crosslinker 1 and 1 wt% crosslinker 2. Crosslinker 1 is polyethyleneimine (PEI), and crosslinker 2 is a mixture of chromium acetate and zinc acetate in a 1:1 mass ratio. The raw materials also include 1.2 wt% pre-crosslinked particles, which are a mixture of equal weights of flexible colloidal particles KA01, flexible colloidal particles SPG-326, and flexible colloidal particles 220A. The raw materials also include 0.8 wt% polymer, which is AN113SH.
[0050] The preparation method of the variable density low-damage polymer-particle composite gel temporary plugging agent in this embodiment is the same as that in Example 1 and will not be further described.
[0051] In this example, the variable-density, low-damage polymer-particle composite gel temporary plugging agent did not fully gel after aging at 160°C for 24 hours, and the temporary plugging agent still retained a certain degree of fluidity. This is speculated to be due to the difficulty of polymer molecules fully expanding at high salt concentrations. Furthermore, the low polymer concentration results in an insufficient number of polymer molecules participating in the three-dimensional network structure, making it difficult to crosslink and form a uniform, solidified temporary plugging agent with sufficient mechanical properties. Therefore, during system construction, a higher-salt concentration formulation requires more polymer and crosslinker.
[0052] In summary, the variable-density, low-damage polymer-particle composite gel temporary plugging agent of the present invention offers the advantages of adjustable gelling time, complete gel breaking, and good compatibility with brine over a wide temperature range (70-170°C), meeting the needs of actual temporary plugging operations. Furthermore, its relatively low cost makes it suitable for large-scale deployment.
[0053] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the embodiments of the present invention should be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.
Claims
1. A variable density low damage polymer-particle composite gel temporary plugging agent, characterized in that: In terms of mass percentage, it includes 0.5wt% to 30wt% of weighting salt (relative to the mass of water, the same below), and the weighting salt is specifically a combination of one or more of sodium chloride, potassium chloride, sodium formate, potassium formate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate, sodium phosphate, potassium monohydrogen phosphate, potassium dihydrogen phosphate, potassium pyrophosphate, and potassium phosphate; it includes 0.5wt% to 4wt% of polymer, specifically a combination of one or more of AKYPM-6S, KYPM-10, AN113SH, and HENGFLOC81207; it includes 0.5wt% to 2wt% of cross-linking agent 1, specifically polyethyleneimine (PEI); it includes 0.1wt% to 0.5wt% of cross-linking agent 2, specifically a combination of one or more of chromium acetate, zinc acetate, and borax; it also includes 0.5wt% to 2wt% of pre-cross-linked particles, specifically a combination of one or more of flexible colloidal particles KA01, flexible colloidal particles 220A, and flexible colloidal particles SPG-326.
2. The variable density low damage polymer-particle composite gel temporary plugging agent according to claim 1, characterized in that: In terms of mass percentage, the concentration of the weighting salt is 0.5wt% to 30wt%.
3. The variable density low damage polymer-particle composite gel temporary plugging agent according to claim 1, characterized in that: The weighting salt is specifically a combination of one or more of sodium chloride, potassium chloride, sodium formate, potassium formate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate, sodium phosphate, potassium monohydrogen phosphate, potassium dihydrogen phosphate, potassium pyrophosphate, and potassium phosphate.
4. The variable density low damage polymer-particle composite gel temporary plugging agent according to claim 1, characterized in that: The polymer is a compound of one or more of AKYPM-6S, KYPM-10, AN113SH, HENGFLOC81207, HENGFLOC60508, and HENGFLOC70006, with a concentration of 0.5 to 3.5%. The polymer is mainly prepared by polymerizing monomers such as acrylamide (AM) and 2-acrylamido-2-methylpropanesulfonic acid (AMPS).
5. The variable density low damage polymer-particle composite gel temporary plugging agent according to claim 1, characterized in that: The cross-linking agent 1 is polyethyleneimine (PEI) with a mass concentration of 0.5wt% to 2wt%, a molecular weight of PEI of 70,000, and a purity of 50%.
6. The variable density low damage polymer-particle composite gel temporary plugging agent according to claim 1, characterized in that: The cross-linking agent 2 is a compound of one or more of chromium acetate, zinc acetate, and borax, with a mass concentration of 0.1 wt% to 0.5 wt%.
7. The variable density low damage polymer-particle composite gel temporary plugging agent according to claim 1, characterized in that: The pre-cross-linked particles are a compound of one or more of the flexible colloid particles KA01, flexible colloid particles 220A, and flexible colloid particles SPG-326, with a mass concentration of 0.5wt% to 2wt%. They are copolymer materials containing carboxyl groups (-COOH), hydroxyl groups (-OH), and amide groups (-CONH2), have a gel network structure, and can absorb saline of a certain mass concentration to swell.
8. The variable density low damage polymer-particle composite gel temporary plugging agent according to claim 1, characterized in that: The viscosity before gelation is adjustable from 10mPa·s to 22000mPa·s, the curing time is adjustable from 2 to 8h, and the temperature resistance is 80 to 170℃.
9. The variable density low damage polymer-particle composite gel temporary plugging agent according to claim 1, characterized in that: The density of the test liquid is 1.00-1.30 g / cm 3 .
10. The variable density low damage polymer-particle composite gel temporary plugging agent according to claim 1, characterized in that: The composite gel temporary plugging agent can be completely chemically broken at all temperatures.